Managerial Certification for Raudhatul Athfal Principals as an Intervention Strategy to Increase Credibility and Public Enrollment Rates - Permeiningsih (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Raudhatul Athfal (RA) is currently facing an institutional credibility crisis that has resulted in a low national Gross Enrollment Rate (APK) of 7.91%. This study aims to analyze the urgency of strengthening the managerial competency of RA leaders through an evidence-based policy approach, by reviewing research findings, the Ministry of Religious Affairs' 2025–2029 Strategic Plan, and the 2020–2024 BPS. The analysis reveals a serious regulatory contradiction in PMA Number 24 of 2018, which removes the requirement for managerial certification for new madrasas, thus widening the regulatory loophole previously regulated in PMA Number 58 of 2017. This indecisiveness is exacerbated by the Decree of the Director General of Islamic Education Number 1176 of 2024, which only positions assessment as data mapping without judicial binding power. As a result, the mechanism for appointing RA heads by the foundation is trapped in administrative formalities and familial subjectivity. As a strategic recommendation, this study proposes a revision of PMA No. 58 of 2017 to transform managerial certification into a mandatory